PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN REALISTIK UNTUK MENINGKATKAN PENALARAN GEOMETRI SPASIAL SISWA DI SMP NEGERI ARUN LHOKSEUMAWE - Murdani . (Universitas Syiah Kuala, 2012)
AbsractThis qualitative study was to develop realistic mathematical learning device that aims to improve the spatial geometry reasoning for Arun Lhokseumawe Junior High School students of class VIII-1 which consists of 28 students, which was implemented in April 2013. This study begins by developing learning tools that Lesson Plan (RPP), student activity sheet (LKS), Teacher Book (BG), Test Results study (THB). Once validated by the validator and otherwise well, then learning devices tested, in order to obtain the ability of the teacher to manage learning good or very good, qualified learning outcomes test validity, reliability, and sensitivity. Activities for students to learn effectively, individually complete mastery learning is above 65%, in the classical unmet mastery learning is above 85%, and student response above 80% (positive).Keywords: realistic mathematical learning, spatial geometry, and mastery learning